국내 소재·부품전문기업의 기술경쟁력이 기업의 성과에 미치는 영향에 대한 연구 - 장선미(Sun-Mi Chang) (무역연구, 2016)
This paper analyzed the structure and changes in the materials and components industry using Korean industrial and trade data. It also examined the impact of technical competitiveness on firm productivity using firm level data. Results showed that the proportion of the materials and components industry to domestic manufacturing were 38.0% based on the number of businesses, 51.3% based on the number of employees and 44.6% based on production. It turns out that the materials and components industry played an important role in manufacturing since during the period from 1999 to 2014, the number of businesses and employment increased to 45% and 33%, respectively only. However, production increased three-fold to 323%. In the trade of materials and components , exports and imports increased 2.95 times and 1.76 times, respectively and these were higher than the overall manufacturing trade growth rate. The Intra Industry Trade index of the materials industry was 0.626 while that for the components industry was 0.652. which were higher than the average level of the manufacturing sector. The Trade Specialization Index showed that before 2010, the materials and components industry was an import-specialized industry but it changed into that of an export specialized industry since 2011. The regression analysis regarding the impact on business productivity of firm technical competitiveness showed a significant positive affect on the firms’ productivity. Openness was a significant positive factor on productivity. KCI Citation Count: 2